Pliocene Mollusca (Bivalvia, Gastropoda) from the S&#248rsdal Formation, Marine Plain, Vestfold Hills, East Antarctica: taxonomy and implications for Antarctic Pliocene palaeoenvironments - Quilty, PG; Darragh, TA; Gallagher, SJ; Harding, LA (Alcheringa: An Australasian Journal of Palaeontology, 2016)
Pliocene shallow-water marine sediments at Marine Plain (centred on 6837.7ʹS; 7807.8ʹE) and covering approximately 10 km in the Vestfold Hills, East Antarctica, have yielded six species of gastropods, and 11 species of bivalves from two beds within the Srsdal Formation. Most of the material is close to in situ but some specimens have been disturbed from their life position; there is no evidence of significant transport. The gastropods include Nacella concinna (Strebel, 1908), Falsimargarita parvispira Quilty, Darragh, Gallagher & Harding sp. nov., indeterminate species of trochids and naticids, Chlanidota ( Chlanidota ) sp. cf. C. signeyana Powell, 1951, and two species of Trophon/Trophonella . Bivalves include Ennucula sp. aff. E. grayi (dOrbigny, 1846), Aequiyoldia defossata Quilty, Darragh, Gallagher & Harding, sp. nov., Pectunculina sp., Lissarca sp., Austrochlamys anderssoni (Hennig, 1911), Ruthipecten campestris Quilty, Darragh, Gallagher & Harding sp. nov., Adamussium necopinatum Quilty, Darragh, Gallagher & Harding sp. nov., Limatula ( Antarctolima ) sp. cf. L. hodgsoni (Smith, 1907), Cyclocardia magna Quilty, Darragh, Gallagher & Harding sp. nov., ? Hiatella sp. cf. H. arctica (Linnaeus, 1767) and Laternula elliptica (King, 1832). Preservation varies considerably owing to recrystallization, dissolution or distortion through compaction, so several species are left in open nomenclature. Oxygen isotope data indicate that water temperature was 47.5C at the time of shell growth. Many species or species groups are now extinct or have migrated away from the Antarctic to the sub-Antarctic region. An Antarctic mollusc fauna has been characteristic of the region for much of the Cenozoic.